The role of movies in Norwegian textbooks. A study of film as artefact in religious education - Jon Magne Vestøl (Nordidactica: Journal of Humanities and Social Science Education, 2012)
Drawing on perspectives on educational design, this article investigates the role of movies in Norwegian secondary school textbooks on religious education, including teachers’ handbooks and textbook websites. All passages containing references to films or movies have been included in the analysis. The distribution of references indicates that a film is an optional artefact and that movies are drawn mainly from a Western cinematic tradition and are related to topics such as Christianity and ethics. When textbook assignments introduce movies as artefacts mediating the understanding of religious issues, information about the message and the artistic role of the film seems to be downplayed. This indicates a need for reflection on how artefacts such as films are introduced into educational activity.